Legal Challenges Faced by Indonesian Citizens Living Abroad - Ferry Irawan Febriansyah; Ulya Shafa Firdausi; Azis Akbar Ramadhan; Nairo Rizka Nur Hamzah; Putresa Herlinda Septiana; Zulfa Nur Fadhilah (International Journal of Community Service Learning, 2025)
The increasing migration of Indonesian citizens to Malaysia has generated significant legal and social challenges, particularly for undocumented children. Many of these children are born to migrant workers or from unregistered marriages, leaving them without recognized citizenship in either Indonesia or Malaysia. The absence of legal documentation restricts their access to education and healthcare services and exposes them to the risk of deportation upon reaching adulthood. This community service initiative employed a service-learning and counseling approach to address these issues, utilizing a qualitative descriptive research design to gain an in-depth understanding of the challenges faced by undocumented Indonesian children in Malaysia. The program was implemented through several stages, including data collection, situational analysis, program implementation, and impact evaluation. A questionnaire was used to gather participants’ feedback and assess community satisfaction with the intervention. The findings indicate that diplomatic intervention and cross-border policy measures are urgently needed to protect, support, and secure the future of Indonesian children lacking legal citizenship status abroad.